2021
DOI: 10.1038/s41598-021-89672-9
|View full text |Cite
|
Sign up to set email alerts
|

Osteocytes as main responders to low-intensity pulsed ultrasound treatment during fracture healing

Abstract: Ultrasound stimulation is a type of mechanical stress, and low-intensity pulsed ultrasound (LIPUS) devices have been used clinically to promote fracture healing. However, it remains unclear which skeletal cells, in particular osteocytes or osteoblasts, primarily respond to LIPUS stimulation and how they contribute to fracture healing. To examine this, we utilized medaka, whose bone lacks osteocytes, and zebrafish, whose bone has osteocytes, as in vivo models. Fracture healing was accelerated by ultrasound stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…Overexpression of miR-23a-3p inhibits and its downregulation enhances the osteogenic differentiation of BMSCs (Dai et al, 2019). Consistent with previous studies, Zhang X. Y. et al (2021) reported that miR-23a-3p expression was significantly increased in rat models of ONFH. In addition, miR-23a knockdown promoted the viability and osteogenic differentiation of BMSCs and increased the mRNA and protein expression of BMP-2, BMP-4, Runx2, Smad5, Wnt1, and β-catenin in BMSCs and rat models of ONFH.…”
Section: Bone Morphogenetic Protein Signaling Pathwaysupporting
confidence: 87%
See 1 more Smart Citation
“…Overexpression of miR-23a-3p inhibits and its downregulation enhances the osteogenic differentiation of BMSCs (Dai et al, 2019). Consistent with previous studies, Zhang X. Y. et al (2021) reported that miR-23a-3p expression was significantly increased in rat models of ONFH. In addition, miR-23a knockdown promoted the viability and osteogenic differentiation of BMSCs and increased the mRNA and protein expression of BMP-2, BMP-4, Runx2, Smad5, Wnt1, and β-catenin in BMSCs and rat models of ONFH.…”
Section: Bone Morphogenetic Protein Signaling Pathwaysupporting
confidence: 87%
“…Low-intensity pulsed ultrasonography (LIPUS) can enhance osteogenic differentiation of MSCs, stimulate the differentiation and proliferation of osteoblasts, inhibit osteoclasts, improve local blood perfusion and angiogenesis, and accelerate the healing of stress fractures ( Chan et al, 2006 ; Amini et al, 2020 ). Clinical studies have shown significant positive effects of LIPUS in treating fresh ( Shimizu et al, 2021 ) and nonunion ( Jiang et al, 2019 ; Leighton et al, 2021 ) fractures. In addition, LIPUS is considered a non-invasive treatment strategy for ONFH ( Yan et al, 2011 ).…”
Section: Therapeutic Applications Of Growth Factors For Osteonecrosis...mentioning
confidence: 99%
“…LIPUS was shown to enhance ECM synthesis and regeneration and to be a potent stimulator of osteogenic differentiation and is used, e.g., in the context of fracture healing [327][328][329]. Bone mass and maturation is also increased upon LIPUS treatment in different animal models, and it was shown that osteocytes in particular respond to LIPUS treatment [330,331]. Transcriptional analysis in a mouse cell line revealed that approximately 180 genes from clusters related to transcription, cellular secretion and immunity are responsive to the mechanical stimulation [331].…”
Section: May the Force Be With You: Mt And Its Implications For Periodontal Regenerationmentioning
confidence: 99%
“…Bone mass and maturation is also increased upon LIPUS treatment in different animal models, and it was shown that osteocytes in particular respond to LIPUS treatment [330,331]. Transcriptional analysis in a mouse cell line revealed that approximately 180 genes from clusters related to transcription, cellular secretion and immunity are responsive to the mechanical stimulation [331].…”
Section: May the Force Be With You: Mt And Its Implications For Periodontal Regenerationmentioning
confidence: 99%
“…However, the outcomes of implantation and repair relying only on bone-like frames are not ideal, which is also the reason why there has been no breakthrough in the treatment of bone defects in the past 30 years. Therefore, scholars have not only continued related research in the fields of medicine and biology but also performed related research in the fields of acoustics (Shimizu et al, 2021), optics (Bai et al, 2021), heat (Shu and Sugita, 2020), and others.…”
Section: Introductionmentioning
confidence: 99%